BTCAS: A Blockchain-Based Thoroughly Cross-Domain Authentication Scheme. (December 2020) - Zhang, Hongxia; Chen, Xingshu; Lan, Xiao; Jin, Hongjian; Cao, Qi
Abstract: In many real resource access scenarios, the parties who require to establish communication may be unable to effectively identify and verify some authentication messages of the other party due to the use of completely different cryptography settings, making it difficult to authenticate each other in such scenarios. We usually define the above-mentioned problem as "cross-domain authentication". Although many research works have been devoted to solving the problem of entity authentication for cross-domain communication, the problem of "incomplete cross-domain" widely exists in existing works. Existing solutions based on some common underlying cryptography foundations greatly limit the application of such cross-domain authentication schemes. In order to solve the problem of "incomplete cross-domain", this paper proposes a thoroughly cross-domain authentication scheme based on blockchain technology, which can be used by participants from different domains that adopt totally different settings. Our security analysis demonstrates that the scheme is provably secure in the standard model and the experimental results show the efficiency of our scheme.